Răspuns :
Răspuns
Explicație pas cu pas:
a) (a+2b+c)/b = a/b + 2 + c/b = 1/2 + 2 + 3/2 = 4/2 + 2 = 2 + 2 = 4.
b) a+c = 6, b=?
(6+2b)/b = 4
6+2b = 4b
2b = 6
b=3.
a)
[tex]\it \dfrac{a}{b}=\dfrac{1}{2} \Rightarrow a=\dfrac{b}{2}\\ \\ \\ \dfrac{c}{b}=\dfrac{3}{2} \Rightarrow c=\dfrac{3b}{2}\\ \\ \\ a+c=\dfrac{b}{2}+\dfrac{3b}{2} \Rightarrow a+c=\dfrac{4b}{2} \Rightarrow a+c=2b\ \ \ \ (*)[/tex]
[tex]\it \dfrac{a+2b+c}{b} = \dfrac{a+c+2b}{b} \ \stackrel{(*)}{=}\ \dfrac{2b+2b}{b}=\dfrac{4b}{b} =4[/tex]
b)
[tex]\it a+c=6 \stackrel{(*)}{\Longrightarrow}\ 2b=6 \Rightarrow b=3.[/tex]